Does the Welfare State Destroy the Family? Evidence from OECD Member Countries - Martin Halla; Mario Lackner; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We study the effect of the size of the welfare state on family outcomes in OECD member countries. Exploiting exogenous variation in public social spending, due to varying degrees of political fractionalization (i.e. the number of relevant parties involved in the legislative process), we show that an expansion in the welfare state increases the fertility, marriage, and divorce rates with a quantitatively stronger effect on the marriage rate. We conclude that the welfare state supports family formation. Nevertheless, we also find that the welfare state decouples marriage and fertility, and therefore, alters the organization of the family.
Keywords: J12; J13; J18; D1; D62; H31; H53; 330; Marriage; divorce; fertility; welfare state; risk sharing